2019
DOI: 10.1111/let.12332
|View full text |Cite
|
Sign up to set email alerts
|

Diverse earliest Triassic ostracod fauna of the non-microbialite-bearing shallow marine carbonates of the Yangou section, South China

Abstract: Since diverse ostracod faunas in the immediate aftermath of the latest Permian mass extinction are mainly found within Permian–Triassic boundary microbialites (PTBMs), the idea of an ostracod ‘microbial‐related refuge’ has been proposed. Here, we report a diversified earliest Triassic ostracod fauna from the Yangou section in South China, where no PTBMs were deposited, providing evidence inconsistent with this ‘microbial‐related refuge’ hypothesis. In addition, a significant ostracod extinction is recorded, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 75 publications
(166 reference statements)
1
14
0
Order By: Relevance
“…Not only that, the filter-feeding ostracods, occupying a larger morphospace in the microbialite facies, preferred oligotrophic conditions (Forel et al 2011; Horne et al 2011), which is inconsistent with the eutrophic conditions during the extinction interval (Schobben et al 2016). Even for the deposit-feeding ostracods, there are no grazing traces, such as Lamonte trevallis (O'Neil et al 2020), recorded in the microbialites (Forel et al 2013b; Qiu et al 2019). Therefore, the view that microbial mats served as a food source for ostracods is still equivocal, and more supporting evidence is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only that, the filter-feeding ostracods, occupying a larger morphospace in the microbialite facies, preferred oligotrophic conditions (Forel et al 2011; Horne et al 2011), which is inconsistent with the eutrophic conditions during the extinction interval (Schobben et al 2016). Even for the deposit-feeding ostracods, there are no grazing traces, such as Lamonte trevallis (O'Neil et al 2020), recorded in the microbialites (Forel et al 2013b; Qiu et al 2019). Therefore, the view that microbial mats served as a food source for ostracods is still equivocal, and more supporting evidence is required.…”
Section: Discussionmentioning
confidence: 99%
“…Hautmann et al (2015) observed that the bivalve and gastropod species found in microbialites did not differ from those in non-microbialite facies, and therefore, microbial mats cannot truly be considered as refugia. Likewise, relatively diverse, postextinction metazoan communities have been reported from non-microbialite successions (Twitchett et al 2004; Beatty et al 2008), including ostracod assemblages from South China and Iran (Qiu et al 2019; Gliwa et al 2020a,b). Further, the anoxic–dysoxic signal associated with microbialite successions has been reinterpreted to represent reducing conditions within the sediment rather than in the water column (Heindel et al 2018; Kershaw et al 2018), which remained well mixed and oxygenated by wave-induced currents in shallow-marine settings (Tang et al 2017; Heindel et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this hypothesis does explain why certain diverse benthic invertebrates during the Griesbachian are associated with microbialites, it has been contested by numerous recent investigations of fossil ostracod and other invertebrates. Results showed that these taxa also occur in sections where no microbialites were deposited, suggesting that benthic life in the end‐Permian ocean was not necessarily restricted to microbial mat ecosystems (e.g., Foster, Lehrmann, Yu, & Martindale, 2019; Qiu et al, 2019). Recent ichnological studies also suggest similar features (Luo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al (2019) reported a distinct Early Triassic Mass Extinction (ETME) associated with ostracod faunal turnover from a highly diverse and abundant fauna to a unique fauna with extremely low diversity and low abundance in the topmost H. parvus Zone at the Yangou section. Coinciding with this horizon, a faunal turnover of gastropods could also be identified (Figure6), characterized by an abrupt transition from a fauna with low abundance and moderate diversity to a fauna with high abundance and high diversity, showing no evidence of impacts from the ETME.…”
mentioning
confidence: 99%